A novel molecular descriptor for highly efficient (ϕTADF > 90%) transition metal TADF Au(iii) complexes. Issue 36 (10th September 2020) - Wang, Yu; Peng, Qian; Ou, Qi; Lin, Shiyun; Shuai, Zhigang
Abstract : It is generally perceived that a fast reverse intersystem crossing rate of T1 → S1 ( k risc ) is crucial for efficient organic thermally activated delayed fluorescence (TADF) emitters. Abstract : It is generally perceived that a fast reverse intersystem crossing rate of T1 → S1 ( k risc ) is crucial for efficient organic thermally activated delayed fluorescence (TADF) emitters. Herein, we demonstrate the non-radiative decay rate of T1 → S0 ( k Tnr) for transition metal complexes that is even more important. We calculated the interconversion rates among S0, S1 and T1 states for two Au(iii )–TADF complexes with triphenylamine (TPA) as a donor moiety but with quite different quantum efficiencies: one with a moderate efficiency of 79% and the other with a high efficiency of 94%, and we found that the former has a much larger k risc (∼10 10 s −1 ) than the latter (∼10 7 s −1 ). Such contradictions with the conventional picture are attributed to the relatively large k Tnr (∼10 6 s −1 ) for the former, leading to an overall lower quantum efficiency. Thus, we propose a novel molecular design descriptor (the triplet non-radiative decay rate k Tnr) for highly efficient transition metal TADF emitters. Further, we find that tetradentate ligand scaffolds with 5-5-6 membered chelate rings could reduce k Tnr to <10 5 s −1 for Au(iii )–TADF complexes, thereby achieving quantum efficiencies above 90%. Based on this theoretical guideline, we have proposed nine newly designed Au(iii ) complexes and predicted their high TADF efficiency.